The cerebellum and psychiatric disorders: unraveling its role in mental health - Braga-Neto, Pedro; Barbosa dos Santos, Maria Wanessa; Scott, Stephanie Suzanne de Oliveira; Munhoz, Renato Puppi; Novis, Luiz Eduardo; Pedroso, José Luiz; Barsottini, Orlando Graziani Povoas (Arquivos de Neuro-Psiquiatria, 2025)
Several studies describe a strong association between structural and functional abnormalities of the cerebellum and psychiatric disorders. It is possible to find investigations especially in cases of schizophrenia, bipolar disorder, depression, anxiety disorders, attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD). The involvement of the cerebellum in these conditions is also supported by clinical, functional, and structural imaging studies. The present narrative review aims to discuss and highlight the role of the cerebellum in these disorders, gathering evidence on the possible locations and connections of the affected cerebellar areas and their implications in the cognitive, emotional, and behavioral domains.
Keywords: Cerebellum; Mental Disorders; Mental Health